Domestic Violence in the Homes of College Students, New Providence, The Bahamas - Plumridge, Susan J.; Fielding, William J. (International Journal of Bahamian Studies, 2009)
This paper identifies the link between a number of antisocial behaviours and domestic violence in 588 households of college students in Nassau, The Bahamas. The survey indicates that about 21% of college students could be living in homes with domestic violence. Further, domestic violence is associated with other anti-social behaviours which may have adverse affects on household members and ultimately the welfare of the nation. The findings suggest that government policy towards alcohol could be changed to reduce the participation by residents in antisocial behaviours linked to domestic violence.